Reducing CO2 emissions of conventional fuel cars by vehicle photovoltaic roofs. (March 2018) - Lodi, Chiara; Seitsonen, Antti; Paffumi, Elena; De Gennaro, Michele; Huld, Thomas; Malfettani, Stefano
Highlights: Off-cycle CO2 savings from vehicle PV roofs on conventional fuel cars. Vehicle PV roofs on average receive 58% of the available solar radiation. A compact car has a PV production of 41 kWh/year when the solar storage capacity is 15 Ah. CO2 saving estimates range from approximately 1.5–3.5 gCO2 /km. The presented methodology can be applied to other vehicle categories. Abstract: The European Union has adopted a range of policies aiming at reducing greenhouse gas emissions from road transport, including setting binding targets for tailpipe CO2 emissions for new light-duty fleets. The legislative framework for implementing such targets allows taking into account the CO2 savings from innovative technologies that cannot be adequately quantified by the standard test cycle CO2 measurement. This paper presents a methodology to define the average productivity of vehicle-mounted photovoltaic roofs and to quantify the resulting CO2 benefits for conventional combustion engine-powered passenger cars in the European Union. The method relies on the analysis of a large dataset of vehicles activity data, i.e. urban driving patterns acquired with GPS systems, combined with an assessment of the shading effect from physical obstacles and indoor parking. The results show that on average the vehicle photovoltaic roof receives 58% of the available solar radiation in real-world conditions, making it possible to reduce CO2 emissions from passenger cars in a range from 1% to 3%, assuming a storage capacity of 20% of the 12 V battery dedicated to solar energy. This methodology can be applied to other vehicles types, such as light and heavy-duty, as well as to different powertrain configurations, such as hybrid and full electric.